Transcending Institutional Origins: The Homogeneity of Multidimensional Moderate Character Among Prospective Elementary Teachers - Yulianti; Aloysius, Duran Corebima; Wulandari, Diana; Ayu, Hena Dian; Kurniawati, Putri Dwi Retno; Rachmawati, Yani Septia; Fauzan (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to investigate the phenomenon of "Institutional Transcendence" by examining whether institutional origins (public vs. private schools) influence the multidimensional moderate character of prospective elementary teachers. Employing a comparative quantitative approach combined with structural modeling, data were elicited from 76 second-semester students of the Elementary School Teacher Education program. The results of a One-Way ANOVA demonstrate no statistically significant disparity in moderate character levels based on institutional origins (F=0.071, p=0.791 > 0.05). Furthermore, Partial Least Squares Structural Equation Modeling (PLS-SEM) confirms the structural integrity of the multidimensional model (R2 = 0.196), identifying Cultural Adaptability and Conflict Resolution as the most significant drivers of moderation. These findings suggest that the higher education environment acts as a potent "Equalizer," effectively homogenizing values through a shared academic ecosystem. The study concludes that while the "Equalizer" effect successfully aligns cognitive and affective dispositions, a "Knowing to Action Gap" persists, necessitating a pedagogical shift toward experiential "Moral Action" to transform theoretical moderation into decisive civic courage.